2011
DOI: 10.1089/cap.2010.0145
|View full text |Cite
|
Sign up to set email alerts
|

The Pharmacoepidemiology of Antipsychotic Medications for Canadian Children and Adolescents: 2005–2009

Abstract: The use of antipsychotics in Canadian children greatly increased from 2005 to 2009. Comparison of antipsychotic data with psychostimulant and SSRI data shows that there has been a disproportionate increase in antipsychotic use over this interval, despite the lack of approval for pediatric use by Health Canada. Postmarketing surveillance activities of antipsychotic use in children appear appropriate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
61
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(70 citation statements)
references
References 21 publications
9
61
0
Order By: Relevance
“…In 2008, the proportion of prescriptions written by GPs in Manitoba was 73%. 17 The third study, by Pringsheim et al, 30 used IMS Health data (Canadian Disease and Therapeutic Index) to estimate the number of prescription recommendations for antipsychotics in the group aged 17 years and younger. Increases both for SGAs and FGAs were observed, but increases were much more rapid for SGAs.…”
Section: Canadamentioning
confidence: 99%
“…In 2008, the proportion of prescriptions written by GPs in Manitoba was 73%. 17 The third study, by Pringsheim et al, 30 used IMS Health data (Canadian Disease and Therapeutic Index) to estimate the number of prescription recommendations for antipsychotics in the group aged 17 years and younger. Increases both for SGAs and FGAs were observed, but increases were much more rapid for SGAs.…”
Section: Canadamentioning
confidence: 99%
“…36,37 Antipsychotic use, in particular, has shown large increases. 38 Especially notable is their burgeoning off-label use, [39][40][41] including in preschool-aged children. 42 -44 Given the frequency and multiple medication regimens with which psychotropic agents are being prescribed, 36 ED clinicians are likely to encounter children and adolescents taking 1 or many of these medications.…”
Section: Adverse Effects Of Psychiatric Medicationsmentioning
confidence: 99%
“…In Canada, rates of antipsychotic indication for children also increased, by 114 % from 2005 to 2009, while indications for stimulants and antidepressants increased by 36 and 44 %, respectively. Attention-deficit/hyperactivity disorder was the most common indication for antipsychotic use [14]. In Denmark, data on filled selective serotonin reuptake inhibitors obtained for all children aged 5-17 during 1995-2011 demonstrated that prevalence proportion rose from 0.1 per 1,000 children in 1995 to 3.3 in 2011.…”
mentioning
confidence: 99%